UPSKILLING UNIT KESEHATAN SEKOLAH TENTANG PERTOLONGAN PERTAMA PADA KECELAKAAN DI PONDOK PESANTREN MODERN AL-HIJRAH KABUPATEN POLEWALI MANDAR - Hermin Husaeni; Muh Fauzar Al Hijrah; Heriyati Heriyati (Universitas Pahlawan Tuanku Tambusai, 2022)
The School Health Unit (UKS) is one of the units that provide health services to students while studying at Islamic boarding schools. The geographical location of the Al Hijrah Islamic boarding school is on the outskirts of forests and rivers, making the students have to be more careful in carrying out their activities in the pesantren area, especially when taking water in the river and looking for firewood in the forest which often results in injuries and fainting and there is a risk of drowning, but after When an initial survey was conducted, it was found that UKS cadres did not understand how to help students who were injured, fainted and drowned. This was because the UKS pesantren were still new and had never been able to improve the skills of students in providing first aid to students and in the community. The purpose of this community service activity is to improve the skills of students in providing first aid to accidents at Islamic boarding schools. The method used is through demonstrations and practicum in carrying out first aid accidents. The results of the service show that students have skills related to first aid in accidents. This activity received great support from the pesantren management because it was able to develop a school health unit that was able to take a role in providing first aid for accidents to pesantren residents Keywords: Upskilling, First Aid, Accidents.